A Severe Form of Arterial Tortuosity Syndrome Presenting With Significant Airway Obstruction in an Infant. Issue 2 (March 2020) - Dodge-Khatami, Jannika; Simpson, Scott A.; Dodge-Khatami, Ali
We describe a severe form of arterial tortuosity syndrome in a newborn, in which the tortuous course of the aorta masqueraded as a pulmonary artery sling on fetal echocardiogram. The newborn presented with respiratory distress after birth. The clinical course was complicated by extrinsic airway obstruction requiring cardiopulmonary resuscitation. Timely diagnostic work-up in patients with arterial tortuosity syndrome is necessary to plan eventual intervention, and hopefully to prevent complications related to the abnormal vasculature.